2022
DOI: 10.1007/s41449-022-00332-8
|View full text |Cite
|
Sign up to set email alerts
|

Social norms in digital spaces: Conflict reports and implications for technology design in the teleworking context

Abstract: With the increase of telework during the COVID-19 pandemic, employees’ interactions with colleagues have shifted almost exclusively to digital channels. Hence, it is critical to understand the underpinnings of successful collaboration and individual wellbeing in digital working structures. Combining qualitative experience reports and quantitative surveys from 145 teleworkers, this study sheds light on teleworking from a psychological perspective, taking social norms as a conceptual frame. The qualitative repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…A recent study highlighted the benefits associated with teleworking such as greater task fulfillment and improved efficiency at work. On the flip side, this same study identified lower levels of conflict management and impaired team spirit (Diefenbach, 2023). The individualistic manner of teleworking renders it more difficult for employees to collaborate with coworkers and managers, and in turn, to develop trusting interpersonal relationships at work (Adamovic, 2022; Griffith et al , 2003).…”
Section: Introductionmentioning
confidence: 79%
“…A recent study highlighted the benefits associated with teleworking such as greater task fulfillment and improved efficiency at work. On the flip side, this same study identified lower levels of conflict management and impaired team spirit (Diefenbach, 2023). The individualistic manner of teleworking renders it more difficult for employees to collaborate with coworkers and managers, and in turn, to develop trusting interpersonal relationships at work (Adamovic, 2022; Griffith et al , 2003).…”
Section: Introductionmentioning
confidence: 79%
“…In contrast to legal norms (e.g., laws), social norms occur spontaneously rather than being planned deliberately and are enforced informally [17]. Typically, social norms only become evident when conflict arises, i.e., if someone's behavior contradicts our informal understanding of what is appropriate, such as cutting in line, entering an office without knocking, or starting to eat before everyone is seated at the table [18]. The same seems to apply to the digital space.…”
Section: Social Normsmentioning
confidence: 99%